2009
DOI: 10.1158/0008-5472.can-08-4199
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Clock Gene Per1 in Prostate Cancer

Abstract: Circadian rhythms regulate diverse physiologic processes, including homeostatic functions of steroid hormones and their receptors. Perturbations of these rhythms are associated with pathogenic conditions, such as depression, diabetes, and cancer. Androgens play an important role in both normal development and carcinogenesis of the prostate. In the present study, we investigated a potential role for the core clock factor Per1 in the pathogenesis of prostate cancer. Serum-shocked synchronized prostate cancer cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(162 citation statements)
references
References 44 publications
7
152
0
3
Order By: Relevance
“…[28][29][30] PER1 and PER2 also interact with the androgen receptor (AR) or estrogen receptor (ER), respectively, in that PER1 inhibits AR-dependent transcription and PER2 induces ER degradation. 31,32) These findings are consistent with the idea that clock proteins act as key players in the cell cycle and DDR by interacting directly with and regulating the functions of the proteins mediating these processes.…”
Section: The Physiological Functions Of Core Circa-dian Regulatorssupporting
confidence: 87%
“…[28][29][30] PER1 and PER2 also interact with the androgen receptor (AR) or estrogen receptor (ER), respectively, in that PER1 inhibits AR-dependent transcription and PER2 induces ER degradation. 31,32) These findings are consistent with the idea that clock proteins act as key players in the cell cycle and DDR by interacting directly with and regulating the functions of the proteins mediating these processes.…”
Section: The Physiological Functions Of Core Circa-dian Regulatorssupporting
confidence: 87%
“…In human endometrial carcinoma, loss of per1 protein is commonly observed in tumor cells, but not in the adjacent normal cells (24). A metaanalysis of microarray expression studies showed that Per1 is down-regulated in human prostate cancer as compared with normal prostate tissue (18). CK1ε gene expression was found to be overexpressed in six kinds of cancer tissues as compared with adjacent normal tissues (25).…”
Section: Discussionmentioning
confidence: 99%
“…As for circadian genes, Bmal1 was shown to be a positive regulator of tumor growth and metastasis in cancer (17). Moreover, overexpression of per1 in prostate cancer cells causes significant growth inhibition and apoptosis (18). In addition, per2 plays a key role in tumor suppression, controlled by genes such as c-myc and cyclin D1 through the activity of Bmal1/clock heterodimers (19), and Per2 gene overexpression induces cancer cell apoptosis (20).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, clock-deficient mouse strains (notably Per2-deficient mice) have been documented to have increased spontaneous cancer rates in some, but not all studies (Antoch et al, 2013;Fu et al, 2002). This reflects possible increases in DNA damage and supports a role for clock genes as tumor suppressors (Cao et al, 2009;Yang et al, 2009). However, these observations are a simplification: other clock-deficient mice do not show increased cancer rates (Antoch et al, 2008;Gauger and Sancar, 2005), and cell lines from multiple clock-deficient strains possess normal DNA repair properties (Gaddameedhi et al, 2012).…”
Section: Circadian Control Of Cell Divisionmentioning
confidence: 93%